2020
DOI: 10.1038/s41598-020-69027-6
|View full text |Cite
|
Sign up to set email alerts
|

Ultralow power spin–orbit torque magnetization switching induced by a non-epitaxial topological insulator on Si substrates

Abstract: The large spin Hall effect in topological insulators (TIs) is very attractive for ultralow-power spintronic devices. However, evaluation of the spin Hall angle and spin-orbit torque (SOT) of TIs is usually performed on high-quality single-crystalline TI thin films grown on dedicated III-V semiconductor substrates. Here, we report on room-temperature ultralow power SOT magnetization switching of a ferrimagnetic layer by non-epitaxial BiSb TI thin films deposited on Si/SiO 2 substrates. We show that non-epitaxia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 40 publications
2
37
0
Order By: Relevance
“…In order to be compatible with the industry-level manufacture, the topological insulator of BiSb is prepared by the magnetron sputtering method 29 , 46 , and the MTJ stack of Ru(5)/CoFeB(2.5)/MgO(2)/CoFeB(5)/Ta(8)/Ru(7) is in-situ deposited on top of the sputtered BiSb(10) without breaking the vacuum (thickness in nanometers), i.e., all sputtered BiSb-MTJ. The TMR ratio of the all sputtered BiSb-MTJ is around 90%, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In order to be compatible with the industry-level manufacture, the topological insulator of BiSb is prepared by the magnetron sputtering method 29 , 46 , and the MTJ stack of Ru(5)/CoFeB(2.5)/MgO(2)/CoFeB(5)/Ta(8)/Ru(7) is in-situ deposited on top of the sputtered BiSb(10) without breaking the vacuum (thickness in nanometers), i.e., all sputtered BiSb-MTJ. The TMR ratio of the all sputtered BiSb-MTJ is around 90%, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A low tilt can be observed (<2°) between the GaAs substrate and the BiSb layer, which corresponds to the blue family in figure 2b. The [110] direction of the GaAs corresponds to the [11][12][13][14][15][16][17][18][19][20] of the BiSb and the c axis is identical for both crystals.…”
mentioning
confidence: 99%
“…[167] In non-epitaxial Bi 2 Sb 3 /CoTb, the critical current density is as low as 7 × 10 4 A cm −2 (Figure 19m). [168] Recently, interfacial PMA magnetic layer was achieved by a thin insertion layer. Mahendra et al successfully prepared a PMA CoFeB layer by sputtering and demonstrated SOT switching in Bi x Se (1-x) /CoFeB heterostructure (Figure 20a,b).…”
Section: Spin-orbit Torque Switching In Topological Insulator/ferromagneticmentioning
confidence: 99%
“…Reproduced under the terms of the Creative Commons CC‐BY license. [ 168 ] Copyright 2020, The Authors. Published by Springer Nature.…”
Section: Spin‐orbit Torque‐induced Magnetization Switching With Low Critical Current Densitymentioning
confidence: 99%
See 1 more Smart Citation